Letrozole Supplementation and the Increased Risk of Elevated Progesterone Levels on Trigger Day - Liu, Rongju; Zhou, Liling; Chen, Xuemei; He, Hongmei; Cai, Zhaowei (Frontiers in Endocrinology, 2022)
Although using letrozole (LE) during IVF/ICSI has many advantages, it remains unclear whether LE induces an increase in progestogen during the late follicular phase. The objective of this study was to investigate whether progesterone levels increased under antagonist protocols supplemented with LE on the trigger day using a retrospective cohort study. The study included 1,133 women who underwent IVF/ICSI cycles from January 2018 to June 2020. After propensity score matching (PSM) for baseline characteristics, 266 patients with gonadotropin-releasing hormone-antagonist (GnRH-ant) were matched to 266 patients with letrozole + GnRH-ant (LE GnRH-ant) (PSM 1 cohort), and 283 patients with gonadotropin-releasing hormone-agonist (GnRH-a) were matched to 283 patients with LE GnRH-ant (PSM 2 cohort). In the PSM 1 cohort, patients in the LE GnRH-a group presented higher progesterone levels (1.22 ± 0.95 ng/mL vs 0.86 ± 0.60 ng/mL, P < 0.001), with a higher proportion of patients with progesterone level > 1.5 ng/mL (24.81% vs 7.52%, P < 0.001). In PSM 2 cohort, patients in the LE GnRH-a group presented higher progesterone levels on trigger day (1.23 ± 0.91 ng/mL vs 0.98 ± 0.61 ng/mL, P < 0.001), with a higher proportion of patients with progesterone level > 1.5 ng/mL (25.45% vs 12.70%, P < 0.001). In the PSM 1 cohort, progesterone levels on the trigger day increased by 0.05 ng/mL, with an increase in every retrieved oocyte in the LE GnRH-ant group (β 0.05 ng/mL [95% CI 0.04, 0.06], P < 0.001), whereas an increase of 0.02 ng/mL was observed in the GnRH-ant group (β 0.02 ng/mL [95% CI 0.01, 0.03], P < 0.001), with P for interaction being 0.0018. In the PSM 2 cohort, progesterone levels on the trigger day increased by 0.05 ng/mL with an increase in every retrieved oocyte in the LE GnRH-ant group (β 0.05 ng/mL [95% CI 0.04, 0.06], P < 0.001), whereas an increase of 0.02 ng/mL was observed in the GnRH-a group (β 0.02 ng/mL [95% CI 0.01, 0.03], P < 0.001), with P for interaction being 0.0002. LE supplementation on the antagonist protocols may increase progesterone levels in the late follicular stage.